Experimental diagnostics and static assessment of fire damaged steel structure - Kmeť, Stanislav; Tomko, Michal; Demjan, Ivo (Видавництво Львівської політехніки, 2013)
In the paper are presented the results of diagnostics, tests of materials, numerical modelling and static analysis of the current state of the bearing steel structure of the hall after a fire and design of the actions for the repair of the damaged steel structural members. Подано результати діагностичного випробування матеріалів, числове моделювання і структурний аналіз поточного стану сталевих конструкцій залу після пожежі і запропоновано заходи щодо ремонту пошкоджених елементів сталевої конструкції.
Keywords: steel structure; diagnostics; material tests; modelling; fire; analysis; resistance of structure; renewal; сталеві конструкції; діагностика; випробування матеріалів; моделювання; пожежа, аналіз; міцність конструкції; реконструкція